Anisakid infection levels in fresh and canned cod liver: Significant reduction through liver surface layer removal. (October 2018) - Klapper, Regina; Carballeda-Sangiao, Noelia; Kuhn, Thomas; Jensen, Hannah Malene; Buchmann, Kurt; Gonzalez-Muñoz, Miguel; Karl, Horst
Abstract: Canned liver is a highly valuable and healthy product from the important commercial fish species cod Gadus morhua . Due to high levels of contaminants such as dioxins and dioxin-like PCBs (polychlorinated biphenyls) in cod liver products from the Baltic Sea, the grounds for supply of cod liver were relocated to areas around Iceland in the Irminger Sea with lower levels of contaminants. In the present study, 62 canned samples, as well as 132 fresh cod livers from Greenland and Iceland, were analysed in order to assess the infection levels with anisakid nematode species. High prevalence and abundance of the potentially zoonotic nematode species Anisakis simplex s.s. and Pseudoterranova decipiens s.s. were found in the fresh livers. Lower infection levels in canned livers compared to fresh livers might indicate successful industrial processing measures in order to reduce nematode larvae in the final products. However, two heat stable allergens, Ani s 1 and Ani s 4, were verified from isolated nematode larvae from canned products. The effectiveness of methods to further reduce the number of nematode larvae during industrial processing of cans with cod liver is discussed. Highlights: Canned cod livers and fresh cod livers were examined for anisakid larvae. High abundances were found in fresh livers, lower levels were detected in cans. Zoonotic Anisakis simplex s.s. and Pseudoterranova decipiens s.s. were identified. Heat stable allergens Ani s 1 and Ani s 4 were verified from cans. The removal of liver mesothelium leads to a significant reduction of larvae.